Pengaruh Kepercayaan Merek, Country of Origin, dan Desain Produk pada Minat Beli Mobil - Akhul Yunia Sofa; Yennida Parmariza (Universitas Prasetiya Mulya, 2023)
This study aims to determine the effect of brand trust, country of origin and product design on purschase intention in Mitsubishi Xpander. Respondents in this study were people who had never bought a Mitsubishi Xpander, but already knew about the product. The population in this study is not clearly known. The sampling technique used is the Hair et al technique where the indicator is multiplied by 5 to 10. The number of samples in this study was 119 samples. The data analysis method used is PLS (Partial Least Square) technique through the SmartPLS statistical software, with the research instrument being a questionnaire. The results showed that Brand Trust, Country Of Origin, and Product Design had a positive and significant effect on Purchase Intention in Mitsubishi Xpander.